A Distributed Model: Redefining a Robust Research Subject Advocacy Program at the Harvard Clinical and Translational Science Center. Issue 4 (20th May 2014) - Winkler, Sabune J.; Cagliero, Enrico; Witte, Elizabeth; Bierer, Barbara E.
Abstract The Harvard Clinical and Translational Science Center ("Harvard Catalyst") Research Subject Advocacy (RSA) Program has reengineered subject advocacy, distributing the delivery of advocacy functions through a multi‐institutional, central platform rather than vesting these roles and responsibilities in a single individual functioning as a subject advocate. The program is process‐oriented and output‐driven, drawing on the strengths of participating institutions to engage local stakeholders both in the protection of research subjects and in advocacy for subjects' rights. The program engages stakeholder communities in the collaborative development and distributed delivery of accessible and applicable educational programming and resources. The Harvard Catalyst RSA Program identifies, develops, and supports the sharing and distribution of expertise, education, and resources for the benefit of all institutions, with a particular focus on the frontline: research subjects, researchers, research coordinators, and research nurses.